Francisco Campos and the Brazilian Authoritarianism. A Hidden Dialogue with Carl Schmitt (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
This article propose to analyse the theoretical sources which constitutes the political culture of the Brazilian authoritarianism in the 20th century, principally in the work of Francisco Campos and his connection with the “integralismo” and its catholic conservatism ways. The hypothesis is that the mentioned connection which had inspired the ideological political culture which make possible all the sources and historical conditions to the implementation of the Brazilian dictatorship in the year 1964. This article has analysed the facist inspiration of the Campos´s theory and how it has happened, his hidden dialogue with Carl Schmitt, settling issuing lines of understanding on contemporary authoritarianism whose spreading still proceed, but now standing under new figures, discourses, rhetorics, symbologies and enemies.